Khảo sát ảnh hưởng của thức ăn trên sinh khả dụng của viên kết hợp Metoprolol-Amlodipin 50/5 mg và xác định tương đương sinh học so với viên cùng hoạt chất SelomaxTM 50/5 / Nguyễn Thị Linh Tuyền, Nguyễn Đức Tuấn, Lê Quan Nghiệm - Nguyễn, Thị Linh Tuyền
The film-coated tablets composed of sustained-release metoprolol 50 mg and intermediate release amlodipin 5 mg (metoprolol-amlodipine 50/5 mg) manufactured by Saigon Center for Science and Technology of Pharmacy were estimated for bioavailability in fast and fed conditions its bioequivalence to the reference SelomaxTM 50/5 in healthy volunteers. The bioavailability and bioequivalence of the two oral formulations were studied on 14 healthy volunteers by a single dose, two – treatment, two – period, three – sequence, randomized, crossover design with a two week washout period between the two phases of the study. After dosing, serial blood samples were collected for a period of 120 hours. Plasma harvested from blood was analyzed for metoprolol and amlodipine by liquid chromatography tandem-mass spectrometry (LC-MS/MS) (validated for a sensitivity, selectivity, reproductivity and accuracy). A set of pharmacokinetic parameters including AUC0-t, AUC0-∞, Cmax, Tmax and Ke were determined. No significant difference was observed in Cmax, AUC0-t, AUC0-∞, and Tmax of metoprolol of the test formulation dosed in fast and fed conditions. AUC0-t, AUC0-∞, and Cmax were tested for bioequivalence after Napier logarithm (Ln) – transform of data. No statistically significant difference was found by analysis of variance (ANOVA); 90% confidence interval for test/reference ratio of these parameters was found within bioequivalence acceptance range of 80 – 125%. These statistical inferences led to the conclusion that the two formulations were bioequivalent and the bioavailability of the test formulation were not influenced by food.